ISOLATION AND CHARACTERIZATION OF ERWINIA HERBICOLA ASSOCIATED WITH INTERNAL DISCOLORATION OF TOMATO FRUITS (LYCOPERSICON ESCULENTUM MILL) IN SAUDI ARABIA - Ibrahim, Y. E.; Saleh, M. A. AL- (Emirates Journal of Food and Agriculture, 2017)
Tomato fruits grown in greenhouses were collected from Al?Karj region during summer 2008. Seven bacterial isolates that characterized as Gram negative, short rod?shaped, yellow-pigmented bacterium were isolated and recovered from the internal discoloration tissue of there collected fruits. Symptoms of infected fruits were blackening of the vascular vessels of tissue reached to seeds and lack any external symptoms. Identification and pathogenicity tests of the isolated bacterium were revealed that it belongs to the species Erwinia herbicola. Artificial inoculated showed that red ripe fruits were more affected than other fruit stages. Also, injection method of various tomato fruits were more effective method when compared to other methods tested. Screening the tomato fruits obtained from various cultivars showed significant differences when were inoculated. To our knowledge this is the first report of E. herbicola recovered from tomato fruits in Saudi Arabia.